Dispersion of Carbon Monoxide Pollutant and The Effect of Health (Case Study on Frontage Road Surabaya by Gaussian Line Source Equation Model) - Nurachmawati Meindah Sari; R. Azizah; Lilis Sulistyorini; Endrayana Putut Laksminto Emanuel; Emillia Devi Dwi Rianti; Fuad Ama; Sukma Sahadewa; Agusniar Furkani Listyawati; Ayly Soekanto; Hardiyono Hardiyono (Universitas Wijaya Kusuma Surabaya, 2022)
Air pollution was being a very important problem and danger for human life. This was related to diseases that arise due to motor vehicle emissions, especially carbon monoxide. Simulation of air dispersion models is the one way to study about air quality that is needed in this regard. This study aims to determine the distribution of carbon monoxide pollutants in Ahmad Yani's frontage and to anticipate the dangers of these pollutants to the health of the people living around the research location. This research discussed about the mathematical model of the dispersion of CO that emitted from cars that passed through the frontage road on the Ahmad Yani Street, Surabaya. The method used is direct observation in the field and numerical simulation using a mathematical model, Gaussian Line Source Equation Model (GLSEM). GLSEM had prepared based on the mechanism of transport of pollutants in dispersion, diffusion and advection. With GLSEM we calculated CO gas concentration values for certain heights downwind. We validated the model by comparing numerical results and measurements of CO concentration. We used the R2 test and we got an R2 close to one. We simulated GLSEM by used Fortran programming language and visualized it with Surfer. The results of the visualization in June showed that the pattern of CO gas dispersion was influenced by the direction and speed of the wind. The results obtained are that the distribution of CO pollutants in the Ahmad Yani frontage is horizontal/downwind. CO concentrations at night are higher than during the daytime. From the CO dispersion pattern, we had known that there were dangerous of air around the frontage for people health. We conclude that around the frontage road of the Ahmad Yani highway there is sufficient open air space so that the danger of CO pollutants being emitted can be minimized so that the health of the community, namely pedestrians, motorcycle drivers and the community around the location can be protected.